BADIIY MATNDA QO’LLANGAN KASB-HUNARGA OID SO’ZLAR LINGVOKULTUROLOGIK BIRLIK SIFATIDA - Qurbonov, Davron (Журнал иностранных языков и лингвистики, 2021)
The language of a work of art isinextricablylinkd with fiction, which has centuries of experience in depicting life. For this language of a work of a art is one of the few stratified words related to professional lexicon. and such words require analysis in terms of usage and meaning.